2015
DOI: 10.1111/jace.13808
|View full text |Cite
|
Sign up to set email alerts
|

Soft X‐ray Ptychographic Imaging and Morphological Quantification of Calcium Silicate Hydrates (C–S–H)

Abstract: Morphological details of calcium silicate hydrate (C-S-H) stemming from the hydration process of Portland cement (PC) phases are crucial for understanding the PC-based systems but are still only partially known. Here we introduce the first soft X-ray ptychographic imaging of tricalcium silicate (C 3 S) hydration products. The results are compared using both scanning transmission X-ray and electron transmission microscopy data. The evidence shows that ptychography is a powerful method to visualize the details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…At large q values (i.e., q > 1 nm −1 ), we find, in agreement with experiments, a dependence IðqÞ ∼ q −4 typical of a Porod regime (29), indicating that the C-S-H surfaces have a subnanometric roughness (30). The Porod regime is followed at smaller q by the same q −3 dependence detected in the experiments that extends over more than one order of magnitude in length and that has been reported and discussed in the literature (4,13,27,31). The ranges of wave vectors q ' 0.07-0.9 nm −1 indicate significant spatial correlations and heterogeneities over length scales between 3.5 and ' 40 nm, hence suggesting a prominent role of the mesopores in the SANS data.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…At large q values (i.e., q > 1 nm −1 ), we find, in agreement with experiments, a dependence IðqÞ ∼ q −4 typical of a Porod regime (29), indicating that the C-S-H surfaces have a subnanometric roughness (30). The Porod regime is followed at smaller q by the same q −3 dependence detected in the experiments that extends over more than one order of magnitude in length and that has been reported and discussed in the literature (4,13,27,31). The ranges of wave vectors q ' 0.07-0.9 nm −1 indicate significant spatial correlations and heterogeneities over length scales between 3.5 and ' 40 nm, hence suggesting a prominent role of the mesopores in the SANS data.…”
Section: Resultssupporting
confidence: 76%
“…This trend is more pronounced with increasing overall packing fraction. The structures from the simulations can be compared with small-angle X-ray scattering (SAXS) or SANS data, which are extensively used to characterize and infer texture properties of hardened cement pastes (4,14,17,(25)(26)(27). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrated C 3 S sample was equilibrated with the ambient air for a week in a tightly sealed plastic box prior to the X‐ray measurement. Details of the raw material and hydration products are given elsewhere . The purity of the C 3 S powder was analyzed by X‐ray powder diffraction (Cu K α , λ = 1.54 Å, D2 Phaser; Bruker, Karlsruhe, Germany), no trace carbonation was detected.…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate mathematical treatment of images can provide quantitative data on the structural topology of the material (Allman et al, 2000;Levitz, 2007). In addition, it was recently shown that projection images can also be used to derive scattering curves that are equivalent to those obtained by small-angle scattering techniques (Brisard et al, 2012;Michot et al, 2013;Bae et al, 2015). This is particularly relevant to the study of complex materials as scattering curves are sensitive to the geometrical properties of both heterogeneities and interfaces (Levitz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning imaging, several techniques have recently been developed to access the 3-D structure of complex materials at the nanoscale (Brisard et al, 2012;Bae et al, 2015), microscale or macroscale (Gimenez et al, 2016). Appropriate mathematical treatment of images can provide quantitative data on the structural topology of the material (Allman et al, 2000;Levitz, 2007).…”
Section: Introductionmentioning
confidence: 99%